2005
DOI: 10.1118/1.2147743
|View full text |Cite
|
Sign up to set email alerts
|

Technical and dosimetric aspects of respiratory gating using a pressure‐sensor motion monitoring system

Abstract: This work introduces a gating technique that uses 4DCT to determine gating parameters and to plan gated treatment, and employs a Siemens linear accelerator to deliver the gated treatment. Because of technology incompatibility, the 4DCT scanner (LightSpeed, GE) and the Siemens accelerator require two different motion-monitoring systems. The motion monitoring system (AZ-773V, Anzai Med.) used for the gated delivery utilizes a pressure sensor to detect the external respiratory motion (pressure change) in real tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
112
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(114 citation statements)
references
References 53 publications
1
112
1
Order By: Relevance
“…In the scenario of mixed use of the ANZAI system for 4D CT and RPM for treatment gating, the differences between the two systems may be detrimental to the desired clinic outcome. Previous studies14, 15, 16 compare different types of surrogates based on phantom experiments and show high agreement achievable for both regular and irregular breathing patterns. However, human respiratory motion involves movement in three dimensions rather than the 1D movement as designed in the phantom studies.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the scenario of mixed use of the ANZAI system for 4D CT and RPM for treatment gating, the differences between the two systems may be detrimental to the desired clinic outcome. Previous studies14, 15, 16 compare different types of surrogates based on phantom experiments and show high agreement achievable for both regular and irregular breathing patterns. However, human respiratory motion involves movement in three dimensions rather than the 1D movement as designed in the phantom studies.…”
Section: Introductionmentioning
confidence: 90%
“…Several respiratory monitoring systems using external surrogates are available in the market for the purposes of measuring respiratory motion for 4D CT imaging and gated treatment 5. These systems measure the respiratory motion as the surface movement of abdomen or chest wall (eg, Real‐Time Position Management [RPM],4 C‐RAD,13 GateCT14), or the pressure change in a belt wrapped around the abdomen (eg, ANZAI,15 Bellows16), etc. There is no consensus of which is the best external surrogate with respect to the correlation with the internal tumor motion.…”
Section: Introductionmentioning
confidence: 99%
“…Such devices include, but are not limited to, external marker blocks, ( 13 ) infrared reflector body markers, ( 14 ) as well as strain gauge belts. ( 15 ) Studies have shown that the correlation between internal anatomy markers and external markers are valid, but in extremely limited cases. ( 16 20 ) This correlation was reported to be poor or nonexistent unless the external surrogate measuring the skin surface was near the target volume.…”
Section: Technological Advances For Electromagnetic Trackingmentioning
confidence: 99%
“…One such system, the AZ‐733VI by Anzai Medical Systems (Tokyo, Japan), uses a load cell and elastic belt wrapped around the patient's abdomen to monitor respiration 6. During inhalation, the elastic belt stretches with expansion of the patient's abdomen and the compressive forces are registered on the load cell.…”
Section: Introductionmentioning
confidence: 99%